Anti-inflammatory potentials, membrane stabilizing and xanthine oxidase inhibitory activities of Clerodendrum volibule ethanolic leaf extract on carragenaan- induced inflammation in rats - Olufunmilayo., Olarenwaju; Mary, OLOGE; Idris, Oyemitan; Rufus, AKOMOLAFE; Bola, Akinpelu; Joseph, Apata; EZEKIEL OLUGBENGA, IWALEWA (International Journal of Pharmacology and Toxicology, 2018)
The folkloric use of Clerodendrum volubile P Beauv (Verbenaceae) for treatment of inflammatory conditions in the Southern part of Nigeria has been reported. The anti-inflammatory action of the ethanolic leaf extract on carrageenan-induced rat paw oedema, lipoxygenase and xanthine oxidase inhibitory effects, and membrane stabilizing potential were evaluated. The extract reduced carrageenan-induced rat paw oedema in a dose dependent manner compared to control group. C. volubile inhibited xanthine oxidase activity in a dose - dependent manner; at 0.5 mg/ml it exhibited maximum inhibitory activity of 95.48% while the standard drug, allopurinol exhibited 70 % inhibition. The extract significantly inhibited lipoxygenase activity, with highest activity at 0.4 mg/ml while Quercetin showed maximum inhibition of the enzyme at 0.1 mg/ml. The extract and Acetaminophen exhibited maximum membrane stabilizing activity of 91.85 Â± 0.50% and 94.32 Â± 0.32% at 2.5 mg/ml respectively. These findings provide justification for the traditional use of C. volubile in inflammatory conditions.